Cloning and characterization of Patatin like Protein (PLP), a phospholipase gene involved in salinity stress induced lipid signaling - Kasirajan, Lakshmi; Keerthana Kamaraj; Sheelamary Sebastiar; Selvi Athiappan; Vivitha Maiyilsamy; Manimekalai Ramaswamy (Journal of Sugarcane Research, 2024)
Sugarcane (Saccharum spp.) is a large perennial grass that is cultivated in tropical, semi-tropical, and subtropical regions of the world. Salinity stress is one of the important abiotic stresses limiting crop growth and productivity. It involves numerous changes in the physiological and metabolic processes, depending on severity, stage of the crop and duration of the stress. Plasma membranes are the primary sites where stress signals are perceived and transmitted for rapid gene expression/enzyme activity. Lipid signaling is one such perfect mechanism for the transmission of information between plasma membrane, cytosol, organelles, particularly nucleus and has found an integral place in stress signaling in plants. Phospholipases (PLs) constitute a family of lipidhydrolyzing enzymes that catalyze lipid remodeling and generate rapid responses to environmental cues. In this study we have cloned and characterized Patatin like Protein (PLP) a phospholipase gene from Erianthus. The saline (8 ds/m) treated sugarcane hybrids such as Co 11015 and Co 12009 along with Erianthus was used for estimation of the copy number of PLP in various tissues. Our results showed that, the leaves of Co 11015 had high copy number of PLP followed by the leaf tissues of Erianthus.This study aids in understanding of PLP gene expression involved in salinity stress induced lipid signaling.